Integrating Constructivist, Assessment, and Cultural Dimensions in EFL Writing Pedagogy - Jusak Patty (ELITE: Journal of English Language and Literature, 2025)
This narrative literature review investigates the integration of cognitive-constructivist, social-collaborative, assessment-based, and cultural-rhetorical frameworks to enhance English as a Foreign Language (EFL) writing instruction. Addressing persistent gaps between theoretical knowledge and classroom implementation, this study synthesizes empirical evidence from 2020 to 2025 to develop an integrated pedagogical framework. The methodology employed a literature search across multiple databases (JSTOR, Google Scholar, ERIC, Web of Science, Scopus) using specified conceptual clusters, with thematic analysis conducted through a three-phase synthesis approach involving comparative methods, critical evaluation, and theoretical integration. Findings demonstrate that when systematically integrated, cognitive self-regulation strategies and social collaborative processes produce synergistic effects on writing complexity, accuracy, and fluency. Assessment effectiveness emerges through differentiated approaches combining formative, summative, and dynamic evaluation methods across proficiency levels. Cultural-rhetorical analysis reveals that learners' first language traditions significantly influence second language rhetorical choices, requiring explicit, culturally adaptive pedagogical interventions. The synthesis identifies professional development, reflective practice, and communities of practice as essential mechanisms for sustainable theory-to-practice translation. The study contributes an initial conceptual framework for understanding multidimensional approaches to EFL writing instruction, though geographic bias toward East Asian contexts and methodological limitations constrain generalizability. Future research should prioritize longitudinal investigations, implementation science methodologies, and collaborative inquiry approaches to develop a scalable, culturally inclusive writing pedagogy that effectively serves diverse learner populations across varied institutional contexts.